2013
DOI: 10.2172/1110475
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Occupant Behavior in Achieving Net Zero Energy: A Demonstration Project at Fort Carson

Abstract: SummaryHow occupants interact with their buildings needs to be a key consideration for all green building planning, design, operations and decision-making. Research on the performance of green buildings in recent years has placed greater emphasis on the need and opportunity to better understand the roles of occupants and the factors that shape their behavior, including default conditions, institutional frameworks, organizational culture, peer pressure and more. Understanding the relative impact of technology-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…Hence, the collaboration between the Malaysian construction industry, organisation management, and the workers is a key objective towards efficient energy use. This is in line with Judd et al ’s (2013) opinion that adequate awareness and training should be carried out regularly by stakeholders and the organisation’s management, to enable occupants understand the effect of their behaviour towards energy consumption.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Hence, the collaboration between the Malaysian construction industry, organisation management, and the workers is a key objective towards efficient energy use. This is in line with Judd et al ’s (2013) opinion that adequate awareness and training should be carried out regularly by stakeholders and the organisation’s management, to enable occupants understand the effect of their behaviour towards energy consumption.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, interviewees suggested that integrated green building design, development of energy savings action plans, implementation of the plans, and monitoring and evaluation of EE behaviour of occupants are the key strategies for reducing occupants’ energy use in Malaysia’s green office buildings. This corresponds to Judd et al (2013) opinion that energy use control is a collective effort that should be followed continuously. Furthermore, organisations should appoint a supervisor who could implement and monitor the energy use of occupants in green office buildings.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Buna göre, ısıtma ve soğutmaya bağlı konfor sıcaklıkları, günışığı kontrolü ve HVAC işletim zaman cetvelinin kontrolü ile sınırlı davranış profilleri üzerinden bakıldığında, bu kontrollerin enerji korunumuna etkisinin yaklaşık %50 olduğu ortaya çıkmıştır. Bir başka araştırmada [10], ofis kullanıcıları enerji tüketimini etkileyen davranışları (yapay aydınlatmanın kontrolü, iç ortam sıcaklığına ilişkin termostat kontrolü, güneş kazançlarının kontrolü, giyim düzeyinin kontrolü, vb.) ile ilgili olarak kullanıcılar bilgilendirildikten sonra, önceki davranışlarına göre %65 ile %92 arasındaki oranlarda, enerji korunumu lehinde iyileşme gözlenmiş olduğu aktarılmaktadır.…”
Section: Gi̇ri̇ş (Introduction)unclassified